2011
DOI: 10.3928/19425864-20100930-02
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Measures of Posterior Talar Glide and Ankle Dorsiflexion Range of Motion

Abstract: Restrictions in posterior talar glide may lead to decreases in dorsiflexion range of motion (ROM). Restricted posterior talar glide and dorsiflexion ROM have been described in the literature, but little is known about the relationships between them. The purpose of this study was to examine the relationship between 4 dorsiflexion ROM measurements and talar glide as measured manually by the posterior talar glide test (PTGT) and posterior talar displacement as measured by an arthrometer. Forty-seven participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
1
13
1
2
Order By: Relevance
“…The narrower stance could have limited participants' ability to lunge forward during the test, and, in addition, if they maintained both heels in contact with the floor during the test, this could have prevented 1 side from reaching full ROM due to more limited ROM on the other side. The WB ROM measured in our study was indeed greater than the range measured in these previous studies, 23,24,30 and we believe these differences in measurement technique are at least partly responsible.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The narrower stance could have limited participants' ability to lunge forward during the test, and, in addition, if they maintained both heels in contact with the floor during the test, this could have prevented 1 side from reaching full ROM due to more limited ROM on the other side. The WB ROM measured in our study was indeed greater than the range measured in these previous studies, 23,24,30 and we believe these differences in measurement technique are at least partly responsible.…”
Section: Discussioncontrasting
confidence: 54%
“…Consequently, it seems important to examine whether the frequent assumption of bilateral symmetry in ROM applies to WB DF ROM as well. Two recent investigations 23,24 of bilateral WB DF ROM in healthy participants have indicated that, although side-toside differences are common, they do not favor either side, and thus, overall, WB ROM is bilaterally symmetrical. Nevertheless, the actual range measured in these 2 studies seems less than that measured in previous research.…”
mentioning
confidence: 97%
“…It is only necessary for the implementation of this measurement, finding the tibial tuberosity for stabilizing the smartphone in a weight-bearing position. The inclinometer uses a digital display to report the angle of decline (Cosby & Hertel, 2011). Despite the high intraclass correlation coefficient values for the goniometer and inclinometer, there is no universal agreement on the choice of one method over the other (Konor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Para la implantación de estas medidas es suficiente con encontrar la tuberosidad tibial para estabilizar el Smartphone en posición de carga. El inclinómetro es un dispositivo digital para marcar el ángulo de declinación (17). Además de la alta correlación intraclase no existe ningún otro método universal para primar la elección de un método sobre otro (11).…”
Section: Introductionunclassified